Immunoelectron microscopic localization of penicillinase in Bacillus licheniformis. - Ghosh, A (1979)
Penicillinase was localized in log-phase cells of Bacillus licheniformis 749/C by labeling with ferritin-anti-penicillinase immunoglobulin G conjugate. Mildly fixed homogenized cells, isolated subcellular fractions, and frozen thin sections were labeled. The label was distributed in discrete patches in the cell envelope. The patches extended from the inside part of the membrane to the outside part of the wall. The inside part of the membrane was labeled more extensively than the outside part. The cytoplasm also bound some ferritin-immunoglobulin G conjugate. Immunoelectrophoresis and biochemical assay of cytosol material suggest that the cytoplasmic antigenic sites are a protease-sensitive form of penicillinase.